(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Background: A reasonably correct estimation of age in elderly people is essential in legal, medical, social and administrative matters. Skulls are usually well preserved in decomposed, mutilated state or in fragmentary bodies. Sagittal suture has a very wide range of fusion. The aim of this study is to collect data of sagittal suture fusion of male and female and comparing with each other, so the more appropriate estimation of age can occur by including sexual dimorphism of sagittal sutural fusion. Material and Methods: This study was conducted in 100 autopsy cases of Department of Forensic Medicine, S.M.S. Medical College & Attached Hospital, Jaipur of aged between 20 to 70 yrs, With making group of male and female for each year of age. The obliteration of the sutures was ascertained endocranially as well as ectocranially. The Sagittal suture was studied in four parts and Scale for closure is studied by Acsadi-Nemeskeri complex method Results: Ectocranially the start of fusion of sagittal suture was observed at the age of 51-60 yrs age group in females and in 46-50 yrs in males and endocranially at 31-40 yrs in males and 41-50 yrs in females. Conclusion: When comparison between males and female subjects for ectocranially closure were made, closure was earlier in males. Completion is perfected at the age of 61-70 years. The study showed that fusion of endocranium began first on S4 & last on S1 in both sexes. Though consensus of opinion in our country is that the obliteration of the skull sutures in females is somewhat earlier than that of males, in the present study no such pattern in difference was noticed in endocrinal sutural fusion.